The Impact of Syrian Developments on the National Security of Neighboring Countries - Damirchi, Seyyed Mahmoud Seyyedi; Ridwan, Muhammad (Budapest International Research and Critics University, 2024)
The aim of this research is to examine the political-security relations between Iran and Turkey in the context of developments in Syria from 2010 to 2019. Using a descriptive-analytical method and the theory of defensive realism (threat balance), this study shows that the developments in Syria during these years have profoundly affected the political-security relations between the two countries. Following the Syrian crisis and the emergence of extremist groups, the relationship between Iran and Turkey, which had moved towards competition and mild interaction from 2002 to 2010, shifted to a threat-oriented approach after 2010. Iran's support for Iranian-backed rebels and Turkey's position in the Western-Arab front aimed at overthrowing the Syrian regime have intensified the differences in viewpoints and approaches between the two countries.